2004
DOI: 10.1029/2003jd003965
|View full text |Cite
|
Sign up to set email alerts
|

A study of the NOx dependence of isoprene oxidation

Abstract: [1] A large set of isoprene and isoprene oxidation product concentration data from four North American sites was examined to assess the NO x dependence of the daytime oxidation of isoprene. Sites that represent a wide range of NO x (50 ppt to 30 ppb) were studied and include the Dickson, Tennessee, and Cornelia Fort Air Park sites during the 1999 Southern Oxidants Study, the Pellston, Michigan, site during the 1998 PROPHET summer intensive, and the Kejimkujik National Park site during the Atlantic 1996 study. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
45
4

Year Published

2006
2006
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(51 citation statements)
references
References 57 publications
2
45
4
Order By: Relevance
“…The rate of isoprene oxidation by OH is also dependent on NO x mixing ratios in a non-linear way. Barket et al (2004) found a crossover from NO x -sensitive to VOC-sensitive conditions at ∼8 ppb of NO x comparing four North American sites. At low NO x conditions, peroxy radicals terminate via self-reaction and reaction with HO 2 .…”
Section: Isoprene Oxidation Pathways: Change Frommentioning
confidence: 99%
“…The rate of isoprene oxidation by OH is also dependent on NO x mixing ratios in a non-linear way. Barket et al (2004) found a crossover from NO x -sensitive to VOC-sensitive conditions at ∼8 ppb of NO x comparing four North American sites. At low NO x conditions, peroxy radicals terminate via self-reaction and reaction with HO 2 .…”
Section: Isoprene Oxidation Pathways: Change Frommentioning
confidence: 99%
“…Too high isoprene and MVK would fit to the overestimation of HCHO in the Lagrange as well as the steady state model over land, while a higher dry deposition alone cannot alleviate the discrepancy over the sea. Regarding the representation of isoprene chemistry in the used chemical mechanism some authors have reported that there can be a strong dependency of the product yields of isoprene oxidation on the complexity of the applied condensed mechanism (Paulson and Seinfeld, 1992;Barket et al, 2004;Fan and Zhang, 2004). Pöschl et al (2000) conclude that a box model with the condensed Mainz Isoprene Mechanism (MIM) included also in MECCA v0.1p produces rather lower organic peroxide mixing ratios under tropical low NO x conditions compared to the extended Master Chemical Mechanism (MCM).…”
Section: Errant Sources or Sinks Of Organic Peroxidesmentioning
confidence: 99%
“…During the day, (MVK+MACR)/ISO is mainly driven by the OH chemistry, which destroys isoprene while producing (and concurrently destroying) MVK and MACR. As for every reactive scalar, the vertical profile of (MVK+MACR)/ISO is a function of turbulent mixing, surface deposition, distance from the emission source (transport time), and photochemical degradation (Montzka et al, 1995;Biesenthal et al, 1998;Barket et al, 2004).…”
Section: (Mvk+macr)/iso Ratios and Implications For Chemistry And Tramentioning
confidence: 99%